(untitled) (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2026)
Classification and epidemiological significance of drug resistance Drug resistance is the loss of the ability of microorganisms to be exposed to the standard or usual therapeutic concentration of a drug used for treatment [1]. This situation sharply reduces the effectiveness of treating infectious diseases, aggravates the course of the disease, increases mortality rates, and places a significant economic burden on the healthcare system [2].